Cost distribution and equity of climate policy in Switzerland - Florian Landis (Swiss Journal of Economics and Statistics, 2019)
Swiss targets for climate policy require significant reductions of emissions by 2050. While such reductions can be achieved in a cost-efficient manner by employing taxes on greenhouse gas emissions, such taxes tend to lead to a regressive distribution of policy cost among households. To counteract such a regressive outcome, tax revenue may be recycled in a progressive way. This paper uses a computable general equilibrium model coupled with a microsimulation of household income and expenditure to examine the policy cost of different carbon tax policies and their distribution across households. I find that in the absence of revenue recycling, emission taxation leads to a regressive distribution of policy cost. I analyze different revenue recycling schemes (per-capita lump-sum transfers, reductions in labor taxation, and reductions in VAT taxation of necessary commodities) and their ability to avoid regressive outcomes.
Keywords: 330; Cost-effectiveness; Computable general equilibrium; Microsimulation; Climate policy; Distributional impacts